Survival of the funkiest Max Stone and Ruby Jones 2 - "Adlam, Frances" (Hawthorn; Mimosa McGraw-Hill, 2007)
Max and Ruby have won a place on THE BRAIN, the newest, coolest TV survivor show. To get through to the next round, they have to sing and dance. How can they compete against groovy DJ Hip and his partner Tabitha? And what about Demelza who sings opera?
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Reality television programs